Envelope proteins and replication of vesicular stomatitis virus: in vivo effects of RNA+ temperature-sensitive mutations on viral RNA synthesis. - Martinet, C (1979)
Temperature-sensitive (ts) mutants of vesicular stomatitis virus belonging to complementation groups III and V were investigated for their in vivo RNA synthesis. The sucrose gradient patterns of the RNA species which they produced at nonpermissive temperature (39.2 degrees C) were systematically compared under different experimental conditions: variation of input multiplicity and of time of infection, superinfection with T particles, and temperature shifts. Finally, a more precise analysis of the various RNA species synthesized was carried out. It appeared that the characteristics of RNA synthesis specified at 39.2 degrees C by tsIII or tsV mutants differed from the normal RNA synthesis of vesicular stomatitis virus wild type. Their common depression at 39.2 degrees C in virion-like RNA (38S) production--i.e., so-called genome replication--was tentatively paralleled with the concomitant ts events which have been previously shown to affect the two viral envelope proteins. An overproduction of the RNA transcripts was described for mutants in group III and posed the question of a regulation process to determine the amount of RNA to be transcribed.